2012
DOI: 10.1071/zo12121
|View full text |Cite
|
Sign up to set email alerts
|

Movements and cumulative range size of the platypus (Ornithorhynchus anatinus) inferred from mark–recapture studies

Abstract: The extent of mammalian movements often varies with size, sex and/or reproductive status. Fyke nets were set along streams and rivers near Melbourne (southern Victoria) from the mid-1990s to 2007, and in the Wimmera River catchment (western Victoria) from 1997 to 2005, to assess how far platypus of different age and sex classes travelled between captures and over longer periods. The mean distance between consecutive captures of adults did not vary significantly as intervals increased from 1–3 months to >3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 34 publications
5
22
0
Order By: Relevance
“…Suggested causes of failure to recapture certain individuals during longitudinal live capture studies have focussed on a likely high degree of mobility of certain individuals, including individuals with large ranges, individuals with a nomadic or roving breeding strategy, nonbreeding individuals unable to find a vacant home range, and transient occupation of an area (Grant, 2004;Bethge, 2009;Serena & Williams, 2013). Such explanations would be consistent with certain platypuses not being detected in this study.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Suggested causes of failure to recapture certain individuals during longitudinal live capture studies have focussed on a likely high degree of mobility of certain individuals, including individuals with large ranges, individuals with a nomadic or roving breeding strategy, nonbreeding individuals unable to find a vacant home range, and transient occupation of an area (Grant, 2004;Bethge, 2009;Serena & Williams, 2013). Such explanations would be consistent with certain platypuses not being detected in this study.…”
Section: Discussionsupporting
confidence: 68%
“…Importantly, during the 13 months of the study, the detection rates of platypuses microchipped at the monitoring sites (72% of the platypuses microchipped in 2011-2012 and 43% of those microchipped in [2007][2008] were similar to the recapture rates achieved during repeated live capture studies performed by Grant (2004) over ~30 years and Serena & Williams (2013) in two areas over ~8 and 12 years. The results of the direction of movement investigations, the absence of a significant effect of length of monitoring on the number of platypus observations at each site and for each individual platypus, and the regular and frequent observations from two platypuses further reinforce our conclusion.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…These observations are consistent with an underlying pattern of limited dispersal of (at least some) relatives. This is somewhat surprising given that previous studies using mark-recapture approaches in the Shoalhaven River (Grant, 2004b;Bino and Grant, 2015) and other streams (Serena, 2012;Serena et al, 2014) have reported the dispersal of a high proportion of juveniles, especially males, few recaptures of adult males, and the continued capture of unmarked males and females. Of all the pairs of relatives we sampled at the same site, most were female-female or male-female, and not male-male (there are only three male-male relative pairs in Table S4), which is consistent with male-biased dispersal.…”
Section: Discussionmentioning
confidence: 88%